2017
DOI: 10.1371/journal.pone.0171528
|View full text |Cite
|
Sign up to set email alerts
|

QTLs associated with agronomic traits in the Attila × CDC Go spring wheat population evaluated under conventional management

Abstract: Recently, we investigated the effect of the wheat 90K single nucleotide polymorphic (SNP) array and three gene-specific (Ppd-D1, Vrn-A1 and Rht-B1) markers on quantitative trait loci (QTL) detection in a recombinant inbred lines (RILs) population derived from a cross between two spring wheat (Triticum aestivum L.) cultivars, ‘Attila’ and ‘CDC Go’, and evaluated for eight agronomic traits at three environments under organic management. The objectives of the present study were to investigate the effect of conven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 48 publications
(77 reference statements)
6
33
0
1
Order By: Relevance
“…The marker Kukri_ rep_c68594_530 (12.7 Mb) on 4D associated with FE in our study was also reported in the same region linked to Rht-D1 (Sun et al, 2017). In addition, the marker Kukri_ C12384_430 associated with Vrn-A1 reported by Zou et al (2017) was close to the marker BobWhite_c8266_227 (698.5 Mb) linked to FE on 5A in the present study. Regarding SW, to our knowledge, this is the first study to provide evidence of its genetic basis in bread wheat.…”
Section: Association Mapping and Comparison With Previous Researchsupporting
confidence: 86%
See 1 more Smart Citation
“…The marker Kukri_ rep_c68594_530 (12.7 Mb) on 4D associated with FE in our study was also reported in the same region linked to Rht-D1 (Sun et al, 2017). In addition, the marker Kukri_ C12384_430 associated with Vrn-A1 reported by Zou et al (2017) was close to the marker BobWhite_c8266_227 (698.5 Mb) linked to FE on 5A in the present study. Regarding SW, to our knowledge, this is the first study to provide evidence of its genetic basis in bread wheat.…”
Section: Association Mapping and Comparison With Previous Researchsupporting
confidence: 86%
“…Related genomic regions associated with grain yield, GNS, and TKW have been previously reported in almost the entire wheat genome (Deng et al, 2011; Cui et al, 2012; Deng et al, 2017; Guo et al, 2017; Sun et al, 2017; Zou et al, 2017; Liu et al, 2018; Su et al, 2018; Yu et al, 2018; Zhai et al, 2018). In this study, we found significant SNPs markers on 2A, 2B, and 7A for GWS; on 1B, 2A, 2B, and 7A for TKW; and on 1A, 2B, and 2D for GNS.…”
Section: Discussionmentioning
confidence: 94%
“…The best order of markers was generated using both "AutoCheckInversions" and "AutoRipple" commands. Then, we built a consensus map based on fourteen hexaploid wheat mapping populations including the five QTL populations (Carberry/AC Cadillac, Carberry/Vesper, Vesper/ Lillian, Stettler/Vesper and Stettler/Red fife) used in the current leaf rust resistance mapping study and nine others, namely: 8021V2/AC Karma [30], AAC Concord/CDC Hughes, Attila/ CDC Go [31], Carberry/Thatcher, Cutler/AC Barrie [28], Norstar/Capelle Despres [29], Norstar/Manitou [29], Norstar/Winter Manitou [29] and RL4452/AC Domain. In addition to SNP markers, 8021V2/AC Karma was genotyped with 529 microsatellite or simple sequence repeat (SSR) [32][33][34] markers.…”
Section: Plos Onementioning
confidence: 99%
“…Taking into account that the cultivated parental line Svevo is a semi-dwarf cultivar carrying the dwarf allele of this gene (De Santis et al 2018) and Y12-3 is a tall WEW (Peleg et al 2005), we assume that this gene may exhibit a strong effect on all agronomical traits. Moreover, other studies in wheat also showed a possible effect of this gene on GPC, which makes Rht-B1 a strong CG for the detected QTL (Fowler et al 2016; Zou et al 2017). Members of NRT1/PTR family of proton-coupled transporters, which are involved in nitrogen metabolism in different plant species (Fang et al 2013; Naz et al 2017; Castro-Rodriguez et al 2017; Corratge-Faillie and Lacombe 2017) and, hence, influencing protein accumulation, were identified within five QTL intervals in the S×Y population and were selected as promising CGs.…”
Section: Discussionmentioning
confidence: 83%